Agile Service Development Combining Adaptive Methods and Flexible Solutions - Lankhorst, Marc.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Economies around the globe have evolved into being largely service-oriented economies. Consumers no longer just want a printer or a car, they rather ask for a printing service or a mobility service. In addition, service-oriented organizations increasingly exploit new devices, technologies and infrastructures. Agility is the ability to deal with such changing requirements and environments. Agile ways of working embrace change as a positive force and harness it to the organization's competitive advantage. The approach described in this book focuses on the notion of a service as a piece of functionality that offers value to its customers. Instead of solely looking at agility in the context of system or software development, agility is approached in a broader context. The authors illustrate three kinds of agility that can be found in an agile enterprise: business, process and system agility. These three types of agility reinforce each other and establish the foundation for the agile enterprise. Architecture, patterns, models, and all of the best practices in system development contribute to agile service development and building agile applications. This book addresses two audiences. On the one hand, it aims at agile and architecture practitioners who are looking for more agile ways of working in designing and building business services or who are interested in extending and improving their agile methods by using models and model-based architectures. On the other hand, it addresses students of (enterprise) architecture and software development or service science courses, both in computer science and in business administration.
Introducing Agile Service Development -- Agility -- Agile Architecture -- Service Modelling -- Patterns for Agility -- An Agile Way of Working -- Stakeholder Communication -- Adopting Agile Service Development.
Keywords: Economics; Software engineering; Computer science; Information systems; Business planning; Management information systems; Economics/Management Science; Business Information Systems; Information Systems Applications (incl. Internet).; Software Engineering; Models and Principles; Computer Appl. in Administrative Data Processing; Organization/Planning.